Shoreline dynamics for coastal erosion in Qeshm Island, Iran - Moradi, Abbas (2012)
Shorelines positions constantly change due to natural processes and anthropogenic activities. These changes could be a useful proxy for coastal erosion and accretion. Shoreline recession due to coastal erosion is a chronic problem along the coastline of Qeshm Island, Iran. Lack of shoreline change data particularly, recession data has resulted in lack of coastal development setbacks. This problem has lead to many uncertainties in sustainable coastal development plans. Coastal structures and environment have damaged because of absent of setback lines. The purpose of this research is to contribute to establish rational coastal erosion setbacks as effective tool in sustainable coastal management and development through digital shoreline change mapping, and quantification, shoreline position prediction for coastal erosion hazard areas mapping. Multi-source shoreline data, including aerial photographs, high accuracy satellite images, geologic maps, and GPS survey data from 1956 to 2009 year were used. A combination of geomorphologic, statistical, cartographical, and geospatial methods and techniques were applied in four phases. The first phase comprised geomorphic proxy-based shoreline definition, detection and digitization. The second phase was shoreline change mapping and quantification. Phase three consisted of statistical analysis of change data and to generate segment-based change data and shoreline dynamic maps. The fourth phase was prediction of future shoreline positions, creation of coastal erosion hazard maps, and, establishment of coastal setbacks. Six morphological shoreline classes including flat sandy beach, muddy tidal flat, rocky tidal flat, high coastal cliff, high and steep sandy beach, and low coastal cliff were identified. From the results of the first phase it was found that the choice of a suitable geomorphic indicator was influenced by the local and regional geomorphology. The second phase results indicated that the sandy beaches were most eroded with an rage recession rate of -0.72 m/yr. Coastal cliffs retreated at a rate of -0.33 m/yr. The total shoreline recession rate for the entire shoreline was estimated at -0.51 m/yr. The research showed that around 40 percent of shoreline study is suffering from high to very high recession rate. The recession rates were used for coastal erosion hazard area mapping and the establishment of coastal erosion setbacks in phases three and four. A new combined method of Linear Regression Rate and Dynamic Segmentation was developed for shoreline position prediction and establishment of coastal erosion setbacks. This method gave several advantages. Firstly, it utilized the recession rate data of each segment for predicting the shoreline position. Secondly,the predicted shoreline followed the geometric shape of the reference shoreline for each segment and represents a more accurate future shoreline map. The coastal erosion setback lines for next 45 and 60 years were forecasted and showed that many existing coastal structures and properties would be threatened by erosion hazard. This research proposes and used a structured method for shoreline change in morphologically inhomogeneous shorelines. It also can be concluded that accurate shoreline change mapping, quantification, analysis, and its position prediction can assist coastal communities for appropriate management of coastal erosion hazards through establishment of erosion-based coastal development setback lines.